The Relationship between exclusive breastfeeding history and nutritional status of toddlers on the incidence of stunting in toddlers - Destariyani, Elvi; Burhan, Rialike; Andriani, Lusi; Sari, Ade Zayu Cempaka; Utami, Rega Yunike (Alma Ata University Press, 2025)
Background: Stunting is a chronic nutritional problem that impacts the physical growth, cognitive development, and health of children in the future. In 2023, Indonesia still had a high rate of stunting at 21.5%, which is higher than the national goal of 14%. In Bengkulu Province, the prevalence of stunting reached 20.2%, while in North Bengkulu Regency it was 8.7%. One of the areas with a high stunting rate is the Kemumu Health Center, where stunting cases were recorded in 120 toddlers (10.56%) in 2024. Factors that affect the incidence of stunting include the history of exclusive breastfeeding and the nutritional status of toddlers. Objectives: To determine the relationship between exclusive breastfeeding history and nutritional status of toddlers with stunting incidence. Methods: This type of study is a retrospective case-control design. This research was conducted in July 2025. The population of this study is all toddlers whose data were recorded in the register of the Kemu Health Center’s integrated health post (Posyandu). The sample used was 238 toddlers (119 stunted, 119 not stunted) with a simple random sampling technique. The data were analyzed using chi-square.Results: There was a correlation between exclusive breastfeeding history (p=0,000; OR=8,066) and Nutritional Status of Toddlers (p=0,008) with the incidence of stunting. Toddlers who do not get exclusive breastfeeding are eight times more likely to experience stunting. Conclusions: There is a relationship between the history of exclusive breastfeeding and the nutritional status of toddlers with the incidence of stunting in toddlers aged 6-59 months at the Kemu Health Center. It is recommended that to solve the stunting problem, it is essential to provide nutritional information corresponding to the specific needs of toddlers.